«Board Games» Assemblages from Early Agricultural Settlements in South-Eastern Europe - Shatilo, L.O. (Праці Центру пам’яткознавства, 2014)
The article considers the hypothesis that some groups of artefacts
(astragalus, «cones» and objects with a system of holes) dating to
early agricultural period (Neolithic and Chalcolithic) from the territory
of South-Eastern Europe could have been used as equipment for
playing ancient «games» or divination practices. The analysis led to
several conclusions: 1) the objects from South-Eastern Europe are
similar in shape to the artefacts that most researchers consider game
equipment (Ancient World, ethnography); 2) these objects appear in
agricultural societies, where signifi cant changes in the outlook and
self-consciousness of the population could be observed; 3) astragalus,
cones and boards with holes appear in the early Neolithic in the Near
East and in the SEE region, they could have reached South-Eastern
Europe in the process of neolithization; 4) the name «games» for such
items can only be used conventionally. У статті розглядається гіпотеза, згідно якої деякі групи артефактів (астрагали, «конуси»
та предмети з системою лунок) ранньоземлеробського часу (неоліт та енеоліт) з території Південно-Східної Європи могли використовуватися в якості інвентарю для проведення давніх «ігор»або віщувальних практик. Аналіз цієї версії дозволив зробити декілька висновків: 1) предмети з ПСЄпо форміаналогічні артефактам, які більшість дослідників вважає предметами для гри (Стародавній світ, етнографія); 2) подібні предметів з’являються в землеробських культурах, де відбулися суттєві зміни у світогляді населення;3) астрагали, конуси та дошки з системою лунок з’являються в ранньому неоліті на Близькому Сході і в регіон ПСЄ вони
могли потрапити в процесі неолітизації; 4) назва «ігри» для подібних предметів може бути
виключно умовною. В статье рассматривается гипотеза, согласно которой некоторые группы артефактов
(астрагалы, «конусы» и предметы с системой отверстий) раннеземледельческого периода (неолит и энеолит) с территории Юго-Восточной Европы могли использоваться в качестве инвентаря для проведения древних «игр» или гадательных практик. Анализ этой
версии позволил сделать несколько выводов: 1) предметы из Юго-Восточной Европы по
форме аналогичны артефактам, которые большинство исследователей считает предметами для игры (Древний мир, этнография); 2)подобные предметы появляются в земледельческих культурах, где произошли существенные изменения в мировоззрении населения; 3) астрагалы, конусы и доски с системой отверстий появляются в раннем неолите
на Ближнем Востоке, и в регион Юго-Восточной Европы они могли попасть в процессе
неолитизации; 4) название «игры» для подобных предметов может быть исключительно условным.